Examination of the levels of acquiring values to the students of high schools - ÜMMET, DURMUŞ (My University, 2015)
© The Turkish Online Journal of Educational Technology.The purpose of this study is to examine the levels of acquiring values to students in the scope of guidance service in both values education and other educations in high schools. The sample group of study consisted of 300 students continuing their education in 6 high schools in 3 different districts of Istanbul. The data of this study was conducted by personal information form and questionnaire prepared by the researcher to determine how much the students have acquired the values. Examining the obtained results, it was found that students had high scores on the values as \"I do not want people to be lack of justice\", \"I always value when someone does me a favour\" and \"I want everybody to live in peace and at ease\". The obtained results were discussed within the framework of literature and similar studies, and various suggestions were brought forward.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; High school; Value; Values education